2009
DOI: 10.1002/gcc.20744
|View full text |Cite
|
Sign up to set email alerts
|

The use of tetradecanoylphorbol acetate‐stimulated peripheral blood cells enhances the prognostic value of interphase fluorescence in situ hybridization in patients with chronic lymphocytic leukemia

Abstract: Interphase fluorescence in situ hybridization (I-FISH) studies have a remarkable prognostic value in patients with chronic lymphocytic leukemia (CLL). I-FISH studies can be performed either on tetradecanoylphorbol acetate stimulated peripheral blood cells (I-FISH-TPA) or unstimulated peripheral blood mononuclear cells (I-FISH-PBMC). The aim of the study was to evaluate whether this finding was clinically relevant in a group of 235 patients with CLL. Fifty-six patients had both I-FISH-TPA and I-FISH-PBMC result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Wrong conclusions on clone sizes and/or development of the latter are possible, and the impact of the proportion of aberrant cells in CLL on the overall survival was reported in previous studies. [20][21][22] Overall, according to our and previous results, 13,15,16 using TPA stimulation and cell cultivation is to be preferred to iFISH in smears in CLL; also, the possibility to get banding cytogenetic result and by that to pick up unusual CLL-associated aberrations should not be neglected.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Wrong conclusions on clone sizes and/or development of the latter are possible, and the impact of the proportion of aberrant cells in CLL on the overall survival was reported in previous studies. [20][21][22] Overall, according to our and previous results, 13,15,16 using TPA stimulation and cell cultivation is to be preferred to iFISH in smears in CLL; also, the possibility to get banding cytogenetic result and by that to pick up unusual CLL-associated aberrations should not be neglected.…”
Section: Discussionmentioning
confidence: 96%
“…Also, Sánchez and Aventín 15 and Delgado et al 16 found that CLL cases with trisomy 12 have higher proportions of aberrant cells in smears rather than in TPA-cultivated suspension. These unexpected findings in the trisomic cases could be explained by TPA stimulating capacity or by technical problems which may affect the proliferation of neoplastic trisomic CLL cells during cultivation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Especially the latter is a key point of CLL development and relapse [Puiggros et al, 2014]. FISH results have shown that the detection of clonal chromosome aberrations in cases with CLL increased in cultures stimulated with TPA [Sánchez and Aventin, 2007;Delgado et al, 2010]. It is known that clonal aberrations can be better detected by CA in cultures with DSP30/IL2 than with other culture methods (see above).…”
Section: Discussionmentioning
confidence: 99%